Long‐term interventions by conservation and development projects support successful recovery of tropical peatlands in Amazonia - Honorio Coronado, Eurídice N.; Grández Rios, Julio; Águila Pasquel, Jhon; Flores Llampazo, Gerardo; Córdova Oroche, Cesar J.; Reyna Huaymacari, José; Hidalgo Pizango, C. Gabriel; Freitas Alvarado, Luis; Pipa Murayari, Ulises; Isla Reátegui, Gonzalo; López Álvarez, Chris; Loja Aleman, Eva; et al. (People and nature (Hoboken, N.J.), 2025)
Rural communities in Amazonia rely on harvesting Mauritia flexuosa fruit, a dominant peatland palm, for their subsistence and income. However, these palms are felled to harvest the fruits, which has led to reduced resource availability due to the pressure exerted by the increasing fruit demand. As a result, climbing has been proposed as a means to harvest the fruits sustainably. However, the long‐term ecological and socio‐economic impacts of climbing, rather than felling, palms remain unknown. We evaluate whether M. flexuosa populations and fruit production in managed peatland palm swamps have recovered within two rural communities in Peru where climbing to harvest palm fruits was adopted between 1999 and 2002. Since then, these communities have been supported by conservation and development projects. We conducted interviews with community members to assess perceptions of change since the introduction of climbing and carried out forest inventories to estimate changes in two socio‐economic indicators (volume of harvested M. flexuosa fruits and income) and three ecological indicators (pole stem density of M. flexuosa, seedling and sapling density, and the sex ratio of adult palms). Our results reveal that the adoption of climbing has improved the health of the forest stands and incomes in both rural communities. Recovery of M. flexuosa populations was supported by local perceptions of increases in stand productivity, improved values of most indicators within managed stands compared to reference data from unmanaged stands in the region, and continuous recovery of degraded stands over time following the adoption of climbing by both communities. Synthesis and applications. We demonstrate how long‐term conservation and development initiatives can lead to successful outcomes for rural communities and peatland ecosystems. However, urgent adoption of sustainable harvesting techniques, such as the palm climbing in our study, is needed across Amazonia to safeguard the ecological integrity of peatlands, below carbon storage, and livelihoods. This transition will require long‐term collaboration among different stakeholders, affordable management plans, and fair prices for sustainable management for peatland resources. Read the free Plain Language Summary for this article on the Journal blog. Resumen Las comunidades rurales amazónicas dependen de la cosecha de frutos de Mauritia flexuosa, una palmera dominante en las turberas, para su subsistencia e ingresos. Sin embargo, la práctica común de talar estas palmeras para obtener los frutos ha reducido la disponibilidad del recurso debido a la presión ejercida por la creciente demanda de los frutos. Como resultado, se ha propuesto escalar las palmeras para cosechar los frutos de manera sostenible. Sin embargo, los impactos ecológicos y socioeconómicos a largo plazo de esta práctica, en comparación con la tala, aún no se han determinado. Evaluamos la recuperación de las poblaciones de M. flexuosa y la producción de frutos en pantanos de palmeras manejados en turberas en dos comunidades rurales de Perú, donde se adoptó la técnica de la escalada para cosechar los frutos entre 1999 y 2002. Desde entonces, estas comunidades han recibido apoyo de proyectos de conservación y desarrollo. Realizamos entrevistas con miembros de cada comunidad para evaluar sus percepciones de cambio desde la introducción de la escalada como técnica de cosecha y realizamos inventarios forestales para estimar los cambios en dos indicadores socioeconómicos (volumen de frutos cosechados de M. flexuosa e ingresos) y tres indicadores ecológicos (densidad de tallos de M. flexuosa, densidad de plántulas y árboles jóvenes, y proporción de sexos en las palmeras adultas). Nuestros resultados revelan que la adopción de la escalada ha mejorado la salud de los pantanos de palmeras y los ingresos en ambas comunidades rurales. La recuperación de las poblaciones de M. flexuosa estuvo respaldada por percepciones locales de un aumento en la productividad de los pantanos, mejoras en la mayoría de los indicadores dentro de las áreas manejadas en comparación con los datos de referencia de los pantanos no manejados en la región y una recuperación continua de las áreas degradadas a lo largo del tiempo tras la adopción de la escalada por ambas comunidades. Síntesis y aplicaciones. Demostramos que las iniciativas de conservación y desarrollo a largo plazo pueden generar resultados exitosos para las comunidades rurales y los ecosistemas de turberas. Sin embargo, es urgente adoptar técnicas de cosecha sostenibles, como la escalada de palmeras en nuestro estudio, en toda la Amazonía para preservar la integridad ecológica de las turberas, su capacidad de almacenamiento de carbono y los medios de vida de las comunidades. Esta transición requerirá una colaboración continua entre las diferentes partes interesadas, la implementación de planes de manejo asequibles y la garantía de precios justos para la gestión sostenible de los recursos de las turberas. Read the free Plain Language Summary for this article on the Journal blog.